2019
DOI: 10.1063/1.5125125
|View full text |Cite
|
Sign up to set email alerts
|

Lanczos-based equation-of-motion coupled-cluster singles-and-doubles approach to the total photoionization cross section of valence excited states

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The computation of Auger–Meitner decay spectra is very challenging because it requires the inclusion and treatment of an electron in the continuum, which cannot be modeled with the same square-integrable basis functions as the bound states. We have recently presented a computational protocol for AES and RAES based on the restricted active space perturbation theory to second-order (RASPT2) wave function parametrization and the one-center approximation (OCA), termed OCA-RASPT2 . The OCA exploits the spatial locality of the Auger–Meitner decay process and essentially amounts to substituting the challenging and expensive exact two-electron bound-continuum integrals with precalculated one-center (atomic) two-electron integrals. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The computation of Auger–Meitner decay spectra is very challenging because it requires the inclusion and treatment of an electron in the continuum, which cannot be modeled with the same square-integrable basis functions as the bound states. We have recently presented a computational protocol for AES and RAES based on the restricted active space perturbation theory to second-order (RASPT2) wave function parametrization and the one-center approximation (OCA), termed OCA-RASPT2 . The OCA exploits the spatial locality of the Auger–Meitner decay process and essentially amounts to substituting the challenging and expensive exact two-electron bound-continuum integrals with precalculated one-center (atomic) two-electron integrals. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we demonstrated that an analytic continuation procedure based on continued fraction functions could be applied to a TDDFT electronic pseudospectrum in the VUV and inner-shell regions of the spectra, from which an analytic expression for the (averaged) complex dynamic dipole polarizability, α­( z ), was obtained. Computing the electronic spectrum for both the discrete and continuum spectral regions using electronic structure methods relying on L 2 basis sets represents a challenge since the asymptotic behavior of the continuum wave functions is not met by L 2 based wave functions.…”
Section: Theorymentioning
confidence: 99%
“…[19][20][21][22][23][24] The computation of Auger-Meitner decay spectra is very challenging because it requires the inclusion and treatment of an electron in the continuum, which cannot be modeled with the same square-integrable basis functions as the bound states. [25][26][27] We have recently presented a computational protocol for AES and RAES based on the restricted active space perturbation theory to second order (RASPT2) wave function parameterization and the one-center approximation (OCA), termed OCA-RASPT2. 23 The one-center approximation exploits the spatial locality of the Auger-Meitner decay process and essentially amounts to substituting the challenging and expensive exact two-electron bound-continuum integrals with pre-calculated one-center (atomic) two-electron integrals.…”
Section: Introductionmentioning
confidence: 99%